Perbandingan Keterampilan Asuhan Persalinan Normal Mahasiswa Prodi DIII Kebidanan STIKes Karsa Husada Garut Berdasarkan Lahan Praktik - naning Suryani (Jurnal Medika Cendikia, 2015)
Clinical practice workplace is place for Diploma III midwifery students in applying the theory and skills during midwifery clinical practice, obstetric clinical practice so that the midwifery workplace clinical practice being important in learning outcomes obtain learning achievement in Normal Delivery Caregiving. An increasing number of midwifery institutions cause the number of students who undertake clinical practice in the same clinical practice workplace be multiplied so that it becomes the problem to determine workplace clinical practices that are able to provide quality learning. The aim of this study was to determine the skills compareson of Normal Delivery Caregiving from place clinical practice. The research method is a cross-sectional study to STIKes Karsa Husada Garut to 127 students who practice midwifery clinic at the practice field (Hospitals, People health centers and Independent midwives workplace). Data analysis using chi-squared test to see whether there is any effect on the practice fields of learning outcomes Normal Delivery Care. The results showed that there was no positive effect on the Workplace Clinical practice of learning outcomes Normal Delivery Caregivin g seen from the value of p> 0.05. The conclusion of this research is the practice field (Hospitals, People health centers and Independent Midwives workplace) does not effect learning outcomes normal delivery caregiving. Judging from the workplace clinical practice variable practices and Learning outcomes are not significant.